Reamer Irrigator Aspirator Versus Iliac Crest Bone Grafting and Proximal Tibial Curettage: Is There a Difference in Blood Loss and Transfusion Rates?. Issue 4 (April 2022) - Martella, Anthony; Schumaier, Adam P.; Sirignano, Michael N.; Sagi, Henry C.; Wyrick, John D.; Archdeacon, Michael T.
Abstract : Objectives: To compare blood loss and transfusion rates among reamer irrigator aspirator (RIA), iliac crest bone graft (ICBG), and proximal tibial curettage (PTC) for autograft harvest. Design: Retrospective comparative study. Setting: Level 1 trauma center. Patients/Participants: The study included 139 adult patients treated between 2011 and 2018. Interventions: Nonunion repair of the femur or tibia using either RIA (n = 64), ICBG (n = 59), or PTC (n = 16) for autograft. Main Outcome Measurements: Estimated blood loss and transfusion rates. Results: Patient demographics, surgical indications, and medical comorbidities that affect bleeding did not differ among the groups. Estimated blood loss (mL) was significantly higher in the RIA group [RIA: 388 ± 368 (50–2000), ICBG: 286 ± 344 (10–2000), PTC: 196 mL ± 219 (10–700), P < 0.01]. The transfusion rate was also significantly higher in the RIA group (RIA 14%, ICBG 0%, PTC 0%, P < 0.01). The amount of graft obtained was higher in the RIA group (RIA = 48.3 mL, ICBG = 31.0 mL, PTC = 18.8 mL, P < 0.01), and the operative time (hours) was longer in the RIA group (RIA = 2.8, ICBG = 2.6, PTC = 1.9, P = 0.04). Conclusion: Estimated blood loss and transfusion rates were significantly higher in patients undergoing RIA compared with those in patients undergoing ICBG and PTC; however, the incidence of transfusion after RIA (14%) was considerably lower than previous reports. These findings suggest that the risk of transfusion after RIA is present and clinically significant but lower than previously believed, and it is likely affected by the amount of graft obtained and complexity of the nonunion repair. The risk of transfusion should be discussed with patients and the choice of RIA carefully evaluated in patients who have anemia or risk factors of bleeding. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.